Maternal, Fetal, and Placental Selectins in Women With Pre-eclampsia; Association With the Renin-Angiotensin-System - Mistry, Hiten D.; Ogalde, Melissa V. Hott; Broughton Pipkin, Fiona; Escher, Geneviève; Kurlak, Lesia O. (Frontiers in Medicine, 2020)
Selectins (endothelial (E), platelet (P) and leucocytes (L)) are a class of cell adhesion molecules, stimulated in response to inflammation. Pre-eclampsia is characterized by inflammation, and angiotensin II is pro-inflammatory. We hypothesised that circulating maternal and fetal concentrations and placental expression of selectins would be increased in women with pre-eclampsia and would be associated with the angiotensin receptors (AT1R and AT2R). Maternal and fetal blood and placental tissue was collected at delivery from White European normotensive controls (n=17) and women with pre-eclampsia (n=17). Soluble (s) E-, P- and L-selectin protein concentrations were measured by ELISA and placental protein expression was examined by immunohistochemistry. Maternal sE-selectin concentrations were increased in pre-eclampsia (P<0.001); conversely fetal sE- and sP-selectin levels were lower in pre-eclampsia (P<0.05 for both). Staining was mainly localised to the syncytiotrophoblast for all selectins. E-selectin expression was increased, while P-selectin was decreased in placental from pre-eclampsia (P<0.05 for both); no differences were observed for L-selectin expression. Both E- and L-selectin were positively correlated (P<0.008; P<0.02) with AT2R placental expression, whilst P-selectin was negatively associated with AT1R (P<0.005), all only in the pre-eclampsia group. This novel study reports maternal, fetal and placental expression of selectins in pre-eclampsia. The increased E-selectins reflect the endothelial dysfunction, characteristic of pre-eclampsia. In contrast, the reduced P-selectins and the positive association of placental AT2Rs with both E-and L-selectin in pre-eclampsia could be a protective mechanism to limit the endothelial dysfunction.